California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
Justice Cruz Reynoso speaking, Lia Triff Belli, Lt. Governor Leo McCarthy Convention Banner: We the people action for the '80's"